Isopentenyl transferase gene expression offers the positive selection of marker-free transgenic plant of Kalanchoe blossfeldiana - Thirukkumaran, G.; Khan, R.S.; Chin, D.P.; Nakamura, I.; Mii, M. (2009 Springer Science+Business Media B.V., 2009)
The technologies allowing the production of transgenic plants without selectable marker genes, is of great interest in public and environmental safety. For generating such marker-free transgenic plants, possibility has been offered by Multi-Auto-Transformation [MAT] vector system, which combines positive selection, using the isopentenyl transferase (ipt) gene, with a site-specific recombination that generates marker-free plants. In this study Agrobacterium tumefaciens strain EHA105 harboring an ipt-type MAT vector, pMAT21, containing lacZ, gus genes and the removable cassette in the T-DNA region was used to produce marker-free transgenic Kalanchoe blossfeldiana Poelln., employing ipt gene as the selectable marker gene. Co-cultivated explants were cultured on hormone- and selective agent-free MS medium, and 85% of the regenerated shoots showed ipt-shooty phenotype with GUS expression. Forty-one morphologically normal shoots were produced during the subculture. More than ninety percent of the normal shoots were ipt -, gus - but lacZ + as determined by PCR analyses. These results indicate that the ipt phenotype was clearly distinguishable from non-transgenic as well as transgenic marker-free shoots. This study opens interesting perspective for the generation of marker-free transgenic K. blossfeldiana with objective useful transgene.
Keywords: Excision; Multi-auto-transformation (MAT) vector; Removable cassette; Selectable marker; Site-specific recombination